The multiple burdens of zoonoses in low- and middle-income countries (LMICs): why zoonoses are worse for the poor - Grace, Delia (International Livestock Research Institute, 2024)
Introduction: Poor people in LMICs have greater exposure to zoonoses through livestock keeping; living in agricultural communities; interactions with peri-domestic and wild animals; less access to clean water; and, greater vulnerability to climate shocks. Although their consumption of animal source products is low, the quality of these products is poor. In addition to human health burdens, zoonoses reduce livestock productivity and are important barriers to trade in livestock products, as well as causing more difficult to quantify harms such as spillover to wildlife populations.